Temporal analysis of tactics in men's 1500m - Mavroidea, P.; Soulas, D.; Tsiokanos, A.; Giakas, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The 1500m run requires a combination of speed and stamina. There is a limited descriptive knowledge on the tactics of the 1500m run [1, 2]. The purpose of this study was to examine the running behaviour of high class athletes the last 10 years. Methods A temporal analysis of the videotapes recorded from the 1993, 1995, 1999, 2001 and 2003 championships was performed. Specifically, we recorded the times (intervals) of the first 400m, 800m, 1200m, 1400m and total time (1500m) for the first 6 athletes. The speed of each interval was normalised to the average speed of the 1500m run. Results The average of the last ten years showed that the 0m-400m and 800m-1200m intervals are performed at about the average speed of the overall run (99% for 0m-400m and 101% 800m-1200m). The 400m-800m are performed at a slower speed (96%) which was levelled by the final 300m (105%). The 1200m-1400m was performed at a speed of 102% of the average speed while the final 100m was the fastest part (111%). Discussion / Conclusions The tendency the last few years indicates that the athletes run faster the first 400m. This has an opposite effect to the final 300m which are run slower, but remain higher than the average speed. It is remarkable that in 1999 we had the fastest initial 400m and the slowest final 100m. The second and third 400m do not seem to have changed; The 2nd 400m remain at about 96% of the average speed and the 3rd 400m at around 101%.